Music in Sassanid period 224-651 A - Kalthuma Jameel Abdulwahid; Arsan Musa Rashid; Imad Adulqadir Brefkany (QALAAI ZANIST JOURNAL, 2021)
Music has an ancient history. It refers to the presence of a human being on earth, where he learned from nature and imitated sounds around him, and for this he created musical instruments and felt the joy and positive power. Music had a presence in all stages of human history, until it reached the era of the Sasanians and flourished reached the top (the peak of progressiveness). Moreever the music became one of the state's arts and it has a direct relationship in all aspects of religious, political and social life, as well as the interest of the Sassanid kings, especially during the reign of Bahram V) And (Kesra Anushrawan) and (Khosrow Pervez) which led to the advancement of music and the emergence of famous musicians, especially during the reign of Khosrow Parvez, such as the invention of Khusrawaniyat melodies and advanced musical instruments with three types of stringed, wind and percussion, including: the tambour, the tambour, the drum, the flute and the cymbal.